Impact of Job Satisfaction on Moonlighting- Intentions: A Study on IT professionals of Tricity - Malodia, Luxmi; Butail, Priya Kumari (Gyan Management Journal, 2023)
This paper aims to empirically study the relationship and impact of Job  Satisfaction on moonlighting intentions of IT professionals. The present significant theoretical foundation of this study is the ‘Attitudes  and Alternatives Model’ (AAM) of Withdrawal Cognitions. This model  explains turnover due to dissatisfaction in the broader aspect and its related  antecedents (which also include searching for alternative employments  and intending to moonlight) and the possible consequences. The population of the study was IT professionals having a minimum  of two years of experience in the province of Tricity (Chandigarh,  Mohali, and Panchkula). To test the statistical and substantive  significance, primary data from IT professionals have been collected  through reliability-tested scales and analysed using SPSS 26.0.  Purposive sampling has been used to select and collect data from the  respondents who specifically belong to the target population of the  present study.
Keywords: Moonlighting Intentions; Job Satisfaction; Platform Working; Gig Working; Double Employment; Freelancing